Argonne days in World War I - Baker, Horace L. (Horace Leonard), 1893-1948 (University of Missouri Press, 2007)
"A straightforward World War I memoir by Horace Baker, a Mississippi schoolteacher who took ship for France in the spring of 1918 as a private in the American Expeditionary Forces and soon fought with the Thirty-second Division in General Pershing's offensive at the battle of Meuse-Argonne"--Provided by publisher.